How can healthcare organizations improve cost-of-care conversations? A qualitative exploration of clinicians' perspectives. Issue 8 (August 2022) - Sloan, Caroline E.; Gutterman, Sophia; Davis, J. Kelly; Campagna, Ada; Pollak, Kathryn I.; Barks, Mary Carol; Santanam, Taruni; Sharma, Meghana; Grande, David T.; Zafar, S. Yousuf; Ubel, Peter A.
Abstract: Objectives: Clinicians increasingly believe they should discuss costs with their patients. We aimed to learn what strategies clinicians, clinic leaders, and health systems can use to facilitate vital cost-of-care conversations. Methods: We conducted focus groups and semi-structured interviews with outpatient clinicians at two US academic medical centers. Clinicians recalled previous cost conversations and described strategies that they, their clinic, or their health system could use to facilitate cost conversations. Independent coders recorded, transcribed, and coded focus groups and interviews. Results: Twenty-six clinicians participated between December 2019 and July 2020: general internists (23%), neurologists (27%), oncologists (15%), and rheumatologists (35%). Clinicians proposed the following strategies: teach clinicians to initiate cost conversations; systematically collect financial distress information; partner with patients to identify costs; provide accurate insurance coverage and/or out-of-pocket cost information via the electronic health record; develop local lists of lowest-cost pharmacies, laboratories, and subspecialists; hire financial counselors; and reduce indirect costs (e.g., parking). Conclusions: Despite considerable barriers to discussing, identifying, and reducing patient costs, clinicians described a variety of strategies for improving cost communication in the clinic. Practice implications: Health systems and clinic leadership can and should implement these strategies to improve the financial health of the patients they serve. Highlights: Clinicians proposed strategies to facilitate communication about out-of-pocket costs with patients. Health systems can provide clinicians with training to communicate effectively about costs. Health systems can invest in technology to provide accurate information on insurance coverage and out-of-pocket costs. Clinics can collect information on financial distress, identify lowest-cost providers, and hire more financial counselors. Clinicians can partner with patients to identify and reduce indirect medical costs whenever possible.